2021
DOI: 10.1155/2021/8823775
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac May Induce PIA-Independent Biofilm Formation in Staphylococcus aureus Strains

Abstract: Staphylococcus aureus is a pathogen commonly resistant to antibiotics. Biofilm formation is one of the important factors related to its virulence. Non-antibiotics drugs, such as nonsteroidal anti-inflammatory agents (NSAIDs), have been studied as an alternative for treating infections by multiresistant pathogens and biofilm-associated infections. In this study, the effects of NSAID sodium diclofenac on growth inhibition and biofilm formation of S. aureus were evaluated. The minimum inhibitory concentration (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Also, in an earlier study, diclofenac sodium reduced the biofilm formation ability by 50.1% in MDR E. coli which is following our results (Baldiris et al 2016). Likewise, in earlier research similar to our results, diclofenac sodium exhibited an anti-biofilm activity in S. aureus and reduced its pathogenicity (Alves et al 2021). Furthermore, the previous report (Abbas et al 2020) revealed that diclofenac sodium significantly reduced the biofilm formation in S. aureus with a percentage ranging between 22.67 to 70% which is close to some extent to our results.…”
Section: Discussionsupporting
confidence: 92%
“…Also, in an earlier study, diclofenac sodium reduced the biofilm formation ability by 50.1% in MDR E. coli which is following our results (Baldiris et al 2016). Likewise, in earlier research similar to our results, diclofenac sodium exhibited an anti-biofilm activity in S. aureus and reduced its pathogenicity (Alves et al 2021). Furthermore, the previous report (Abbas et al 2020) revealed that diclofenac sodium significantly reduced the biofilm formation in S. aureus with a percentage ranging between 22.67 to 70% which is close to some extent to our results.…”
Section: Discussionsupporting
confidence: 92%
“…Another potential function of the E‐Janus Col/DS film is its antibacterial activity, since DS released from the porous layer is reported to inhibit the DNA synthesis of bacteria [ 21 ] as illustrated in Figure 5h . Staphylococcus aureus, a common foodborne pathogenic microorganism that causes periodontitis, was used to evaluate the antibacterial properties of E‐Janus Col/DS films.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of drugs that can show a greater or lesser degree of activity against microbial pathogens include drugs belonging to the nonsteroidal anti-infammatory class [8,9], antihistamines [10], antineoplastics and antipsychotics/antidepressants [6], anesthetics and statins [7], organometallic compounds, such as auranofn (a drug approved for the treatment of rheumatoid arthritis), and organoselenium compounds, which have diferent pharmacological activities [11]. Among the selenorganic compounds already synthesized, ebselen (2-phenyl-1,2-benzisoselenazol-3(2H)-one) (Figure 1) has been the most studied, mainly due to its antioxidant properties, but also anti-infammatory and antiatherosclerotic properties [12].…”
Section: Introductionmentioning
confidence: 99%